RETRACTED: Assessment of the effect of traffic safety on the on-street parking in case of Uzbekistan - Mamaev G.; Kulmuradov D.; Yuldoshev B. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001